1999
DOI: 10.1074/jbc.274.53.37533
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Pseudomonas aeruginosa Cytochromec 551 by Systematic Amino Acid Substitutions Based on the Structure of Thermophilic Hydrogenobacter thermophilus Cytochrome c 552

Abstract: A heterologous overexpression system for mesophilic Pseudomonas aeruginosa holocytochrome c 551 (PA c 551 ) was established using Escherichia coli as a host organism. Amino acid residues were systematically substituted in three regions of PA c 551 with the corresponding residues from thermophilic Hydrogenobacter thermophilus cytochrome c 552 (HT c 552 ), which has similar main chain folding to PA c 551 , but is more stable to heat. Thermodynamic properties of PA c 551 with one of three single mutations (Phe-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(126 citation statements)
references
References 41 publications
3
123
0
Order By: Relevance
“…The stability of mitochondrial cytochrome c is, however, lower with a denaturation temperature (T m ) of 67°C for the oxidized state (31). Comparisons have been made of the structures and sequences of homologous proteins from thermophiles and mesophiles (32) including a comparative study of cytochrome c 552 from H. thermophilus and the homologous cytochrome c 551 from mesophilic Pseudomonas aeruginosa (33,34). One feature identified that may be important in promoting the thermal stability of H. thermophilus cytochrome c 552 is the high density of hydrophobic side chains in the core of this protein (34).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of mitochondrial cytochrome c is, however, lower with a denaturation temperature (T m ) of 67°C for the oxidized state (31). Comparisons have been made of the structures and sequences of homologous proteins from thermophiles and mesophiles (32) including a comparative study of cytochrome c 552 from H. thermophilus and the homologous cytochrome c 551 from mesophilic Pseudomonas aeruginosa (33,34). One feature identified that may be important in promoting the thermal stability of H. thermophilus cytochrome c 552 is the high density of hydrophobic side chains in the core of this protein (34).…”
Section: Discussionmentioning
confidence: 99%
“…The HT c 552 , PH c 552 , and PA c 551 wild-type proteins, and the reciprocal variants, HT c 552 I78V, PH c 552 V78I, and PA c 551 V78I, were prepared by the method previously described. 6,9,10) We adopted the residue numbering system used for PA c 551 for clarity. The proteins were overexpressed with co-transformed pEC86 carrying the ccmABCDEFGH genes in Escherichia coli JCB387 cells and isolated from periplasmic extracts.…”
Section: Methodsmentioning
confidence: 99%
“…The HT c 552 , PH c 552 , and PA c 551 wild-type proteins, and the variants, HT c 552 S78C, PH c 552 T77C, and PA c 551 S80C, were prepared by a method previously described, 6,8,9) with minor modifications. The proteins were overexpressed with co-transformed pEC86 carrying the ccmABCDEFGH genes in Escherichia coli JCB387 cells and isolated from the periplasmic extracts.…”
Section: 7)mentioning
confidence: 99%
“…8) Data points were corrected for the slope of the baselines for the native and denatured forms, and normalized to calculate the fraction of protein denatured. The fraction denatured was plotted as a function of temperature ( Fig.…”
Section: 7)mentioning
confidence: 99%